Resolving Not to Quit: Evidence That Salient Group Memberships Increase Resilience in a Sensorimotor Task - Green, Jodie; Rees, Tim; Peters, Kim; Sarkar, Mustafa; Haslam, S. Alexander (Frontiers in Psychology, 2018)
There is evidence that the social groups to which people belong can be a source of resilience in challenging times. In this paper, we examine whether social group memberships can also increase resilience in the face of negative performance feedback by encouraging task persistence. In two experiments (Ns = 63, 61) participants completed three rounds of a performance task. In the experimental conditions (but not the control) participants were first asked to reflect on either one or five important social groups of which they were members. In both experiments, participants who reflected on important social groups were more likely to persist in practicing the task after negative performance feedback than those in the control condition. In Experiment 2, there was also evidence of performance improvement after negative feedback for participants in experimental but not control conditions. There was no evidence that self-reported confidence, motivation, or self-efficacy accounted for the observed effects. Overall, this is the first study to provide evidence that salient group memberships can increase resilience in a sensorimotor task. Significantly, the findings suggest that groups are not just a context but also a critical psychological resource for performance following failure feedback.